The association between weekend warrior physical activity pattern and albuminuria in hypertensive patients - Bingquan Xiong; Wenlong Yu; Xinyi Guan; Zhuo Tian; Min Zhu; Huiping Yang; Jiaxin Wang; Yingrui Li; Bin Liu; Yufan Wang; Qiang She (BMC Public Health)
Abstract Background Albuminuria, a critical and sensitive indicator of vascular injury, has been linked to early kidney damage in patients with hypertension. High-quality physical activity (PA) may reduce urinary albumin excretion. Yet, the connection between PA patterns and albuminuria is still not well understood. Methods Albuminuria was identified as urinary albumin/creatinine ratio (ACR) > 30 mg/g. PA was assessed by a series of self-report questionnaires and grouped into inactive PA, insufficient PA, weekend warriors (WWs), and regular PA. Logistic regression was conducted to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) to explore the relationship between PA pattern and albuminuria among hypertensive adults. Subgroup and sensitivity analyses were conducted to verify the robustness of the results. Results This research included 12,961 hypertensive adults (mean age: 54.31 ± 0.24 years), including 6,060 (46.76%) females and 6,901 (53.24%) males. Of them, 2,239 (17.27%) were identified with albuminuria, and 10,722 (82.73%) were without albuminuria. Logistic regression showed that WWs had a 47% lower risk of albuminuria (OR = 0.53,95%CI:0.35–0.80), and regular PA had a 32% decreased risk of albuminuria (OR = 0.68,95%CI:0.56–0.82). However, there were no differences between WWs and regular PA in reducing albuminuria among hypertensive adults. Subgroup analyses showed that these inverse associations of WWs and regular PA with albuminuria were found in hypertensive adults without diabetes. Conclusions Compared with inactive PA, both WWs and regular PA could confer the equivalent benefits on reducing albuminuria among hypertensive adults. These findings highlight the beneficial effect of PA on albuminuria and provide a proven method for those hypertensive adults with a busy lifestyle.